How can semantic annotation help us to analyse the discourse of climate change in online user comments? - Collins, Luke C. (Bern Open Publishing, 2015)
User comments in response to newspaper articles published online offer a unique resource for studying online discourse. The number of comments that articles often elicit poses many methodological challenges and analyses of online user comments have inevitably been cursory when limited to a manual content or thematic analysis. Corpus analysis tools can systematically identify features such as keywords in large datasets. This article reports on the semantic annotation feature of the corpus analysis tool Wmatrix which also allows us to identify key semantic domains. Building on this feature, I introduce a novel method of sampling key comments through an examination of user comment threads taken from The Guardian website on the topic of climate change.